Sub-National Governments’ Participation in the Economic Recovery and Growth Plan (ERGP) in Nigeria - Oladeji, A.; Arawomo, D. F. (African Journal of Stability and Development (AJSD), 2018)
The relative roles of the three tiers of government in public service delivery has emerged as one of the most important topics of open and vigorous debate in Nigeria. Being a federal system of government, there have been increased calls for intergovernmental fiscal relations in the country to be reassessed in light of a widespread belief that although the states and LGAs are assigned primary responsibility for the delivery of basic public services, they are not equipped with adequate revenue resources to fulfil their expenditure obligations. This study examines the prospects and challenges of sub-national governments’ participation in the Economic Recovery and Growth Plan (ERGP) which is the economic blueprint of the current federal government of Nigeria. Among others, the study observes that subnational revenue potential is limited by the inter-jurisdictional mobility of economic agents, with most naturally “local” taxes having low revenue yields. Hence, typically, subnational own-revenue sources are not commensurate with sub-national spending responsibilities, creating a vertical fiscal imbalance usually filled by fiscal transfers from the federal government. Of course, the almost exclusive reliance on federal transfers creates conditions for lack of accountability as sub-national governments may continue to shift blame and responsibility for service delivery to higher tiers of government that control the bulk of government revenues. The study also highlights the political and institutional constraints to sub-national government participation in Economic Development Plans in Nigeria, with suggestions as to how the constraints can be conquered.